Onset of extensive human fire use 50,000 y ago - Shoushu Jiang; Debo Zhao; Stefanie Kaboth-Bahr; Luc Beaufort; Hua Tu; Zhengyao Lu; Zhongjing Cheng; Shanjia Zhang; Yi Zhong; Xiudong Hao; Wenqiang Pei; Guangqiang Cui; et al. (Proceedings of the National Academy of Sciences, 2025)
Fire is a pivotal aspect of human involvement in the carbon cycle. However, the precise timing of the large-scale human fire use remains uncertain. Here, we report a pyrogenic carbon record of East Asian fire history over the past 300,000 y from the East China Sea. This record suggests a rapid increase in fire activity since approximately 50,000 y ago, indicating a decoupling from the monsoon climate, and this pattern is consistent with fire histories in Europe, Southeast Asia, and Papua New Guinea-Australia regions. By integrating extensive archaeological data, we propose that the intensified global expansion of modern human and population growth, coupled with the rising demand for fire use during cold glacial periods, resulted in a significant increase in fire utilization from 50,000 y onward. This suggests that a measurable human imprint on the carbon cycle via fire likely predates the Last Glacial Maximum.